Pengaruh Lingkungan Kerja terhadap Produktivitas Pegawai Dinas Kesehatan Kabupaten Karawang - Hanifah, Aan; Chaerudin, Chaerudin (Peneliti.net, 2024)
This study aims to determine the effect of the work environment on the productivity of district health office employees. This study uses a quantitative approach. Quantitative research aims to develop a mathematical model, where this research does not only use theories taken from the literature or theoretical studies, but is also very important to build hypotheses that have a relationship with the natural phenomena to be studied. Data collection techniques using a questionnaire and tested through a simple linear regression test, test the correlation coefficient and test the coefficient of determination. The results of this study indicate that the effect of the work environment on employee productivity is 23.6% and the remaining 76.4% is not examined in this study.